2021
DOI: 10.1055/s-0041-1731663
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Progenitor Cells Modulate the Phenotype of Smooth Muscle Cells and Increase Their Neointimal Accumulation Following Vascular Injury

Abstract: Background Smooth muscle cells (SMCs) are the main driver of neointima formation and restenosis following vascular injury. In animal models, endothelial progenitor cells (EPCs) accelerate endothelial regeneration and reduce neointima formation after arterial injury; however, EPC-capture stents do not reduce target vessel failure compared with conventional stents. Here we examined the influence of EPCs on features of SMCs pivotal for their impact on injury-induced neointima formation including proliferation, mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 40 publications
0
21
0
Order By: Relevance
“…Local and systemic inflammation plays a key role in the activation of the proliferative process, which consists of the proliferation, migration, and differentiation of vascular smooth muscle cells (VSMCs) as well as the migration of matrix metalloproteinases (MMPs), DNA replication, and extracellular matrix synthesis [25]. Endothelial progenitor cells were shown to take part in the stimulation of the proliferation and migration of VSMCs, which leads to an increase in their neointimal accumulation following vascular wall injury [27]. All these processes result in neointimal hyperplasia [28].…”
Section: General Mechanism Of Restenosismentioning
confidence: 99%
“…Local and systemic inflammation plays a key role in the activation of the proliferative process, which consists of the proliferation, migration, and differentiation of vascular smooth muscle cells (VSMCs) as well as the migration of matrix metalloproteinases (MMPs), DNA replication, and extracellular matrix synthesis [25]. Endothelial progenitor cells were shown to take part in the stimulation of the proliferation and migration of VSMCs, which leads to an increase in their neointimal accumulation following vascular wall injury [27]. All these processes result in neointimal hyperplasia [28].…”
Section: General Mechanism Of Restenosismentioning
confidence: 99%
“…Of note, inflammatory activation of cells with recombinant low-dose TNFα strongly amplified expression and secretion of CXCL12 in SMCs and EPCs. As we have previously observed that EPC-derived microvesicles (MVs, also known as microparticles or extracellular vesicles) alone may modulate key functions of SMCs and as MVs harbor and transfer bioactive substances including chemokines and microRNAs [ 20 , 21 , 22 ], we also evaluated the presence of CXCL12 in MVs. Indeed, a notable amount of CXCL12 could be identified in MVs derived from EPCs (EPC-MV) and SMCs (SMC-MV), indicating that a relevant portion of released CXLC12 is transferred to MVs ( Figure 1 C).…”
Section: Resultsmentioning
confidence: 99%
“…In a recent study, we have shown that heterocellular interaction of EPCs and SMCs results in the alteration of the secretion profile with a selective positive synergy of co-cultivation for certain factors [ 20 ]. Following co-incubation of EPCs and SMCs, we measured not only significantly higher CXCL12 protein levels compared to the respective supernatants of EPC and SMC monocultures but also over-additive absolute values of CXCL12 (803 ± 61 pg/μL) when related to the combined supernatant derived from both monocultures (305 ± 31 pg/μL), indicating a positive synergy of co-cultivation for the release of CXCL12 ( Figure 1 E).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations